Strengthening Capacity through Expansion of Community Participation in Mangrove Ecotourism Management in Pamurbaya - Rahaju, Tjitjik; Suryono, Agus; Mardiyono, Mardiyono; Rochmah, Siti (JPAS (Journal of Public Administration Studies), 2020)
The movement of the public sector in development has become important in relation to the governance agenda (Pomerantz in Bevir,2011;164) . Development failures in many developing countries are due to the presence of insignificant community participation in poverty alleviation (Grindle,2004;526). Surabaya is an example of a city that is trying to continue to empower its people through various activities under Dinas Pertanian dan Ketahanan Pangan.The potential of coastal areas that are rich in mangroves in Surabaya along the East Coast of Surabaya (Pamurbaya) is the choice to empower the community with mangrove ecotourism designn. Theoretically the phenomenon of empowerment in the view of researchers is interesting to study. Considering even though there have been many empowerment programs implemented in Pamurbaya. The existing program has not been able to fully complete community capacity development. Active community participation was also still limited and the achievement of prosperity that needs to be improved.Â